The Dynamics of Adolescent Sexuality: A Comprehensive Study - Jannah, Raudhatul; Budinurdjaja, Pribakti; Febriana, Silvia Kristanti Tri; Arifin, Syamsul; Panghiyangani, Roselina (Graha Primera Saintifika, 2024)
Adolescent sexual behavior is all adolescent behavior that is driven by sexual desire. One of the impacts of risky sexual behavior is STIs in the form of AIDS. Banjarbaru City is one of the cities with the highest prevalence rate of AIDS sufferers aged 15-19 years, namely 28.57%. The aim of this research is to analyze the influence of knowledge, attitudes, parenting patterns and spiritual beliefs on adolescent sexual behavior through intention in Banjarbaru City. This research uses cross sectional. There are 200 samples using the Cluster Proportional Random Sampling technique. The instrument uses a questionnaire. Dependent variable: adolescent sexual behavior. Independent variables: knowledge, attitudes, parenting patterns and spiritual beliefs. Intermediary variable: intention. Analysis uses path analysis. The research results show the p-value of the direct effect on sexual behavior, knowledge variables (p=0.016), parenting patterns (p=0.004) and spiritual beliefs (p=0.005), attitudes (p=0.305). Simultaneously the p-value of all independent variables on sexual behavior (p=0.014). Taken together in the indirect effect, intention was not a significant mediating variable (p=0.159>0.05). The conclusion of this research is that there is a direct effect between knowledge, parenting patterns and spiritual beliefs and there is no direct effect between attitudes towards sexual behavior. Simultaneously, all independent variables have a direct effect on sexual behavior. The indirect effect of intention was not a significant mediation in this study.